(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is devoted to the mesolithic period coverage in the material culture system of the stone age communities of the Zarafshan oasis. It describes the mesolithic period history study in the oasis, the main monuments and their study methods, scientific analysis of archaeological sources and conclusions, the research prospects.